Industrial development survey : (United Nations, 1974)
This is a special issue in a series of industrial development surveys, prepared in response to Economic and Social Council resolution 1030 (XXXVII) in which the Secretary-General was requested to arrange for the preparation of periodic industrial development surveys, and in response to General Assembly resolution 2152 (XXI) and resolution 1 (I) of the Industrial Development Board.